2018
DOI: 10.1108/ijbm-02-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between service quality dimensions, customer satisfaction and loyalty in Turkish banking sector

Abstract: Purpose Using the attitudes of students toward ideal banking services, the purpose of this paper is to examine the structure of banking-related SERVQUAL service dimensions with first-order and second-order confirmatory factors analysis. Following this, a study model was suggested to describe the relationship between the perceptions of students regarding the services provided by their banks and their overall level of satisfaction with the bank. Design/methodology/approach The sample group for the study compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 33 publications
10
75
1
4
Order By: Relevance
“…According to Monferrer et al (2019) customer relations represent a factor in attaining customer loyalty through customer satisfaction because it has the strongest total effect on customers. However, studies, for instance, Kashif and Rehman (2015), Altaf (2017), Yilmaz et al (2018), and Ali and Naeem (2019) conclude that their results cannot be generalized because cultural differences may affect customer loyalty to Islamic banks in various countries.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…According to Monferrer et al (2019) customer relations represent a factor in attaining customer loyalty through customer satisfaction because it has the strongest total effect on customers. However, studies, for instance, Kashif and Rehman (2015), Altaf (2017), Yilmaz et al (2018), and Ali and Naeem (2019) conclude that their results cannot be generalized because cultural differences may affect customer loyalty to Islamic banks in various countries.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Studies of ATM service quality have showed the importance of reliability among the dimensions of retail service quality that positively and significantly predicted customer satisfaction [2,7,19,21]. Therefore, the study proposed hypothesis one (H1) and is stated as:…”
Section: Hypothesesmentioning
confidence: 99%
“…Se esses tangıveis forem inadequados, indisponıveis ou em más condições, os clientes não se sentirão satisfeitos com o serviço do transporte público. Estudos empıŕicos mostraram um efeito positivo da dimensão tangıvel na satisfação em diversos tipos de serviços em companhias aéreas (Leong et al, 2015), hospitais (Calisir et al, 2014), bancos (Yilmaz et al, 2017) e cassinos (Shi et al, 2014). Portanto, a segunda hipótese de pesquisa é formulada: H2: A dimensão Tangıveis tem um efeito positivo na satisfação do usuário de transporte público.…”
Section: Confortounclassified